(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The article describes general aspects of french judicial system and procedural rules on criminal matter, in order to identify privileges of jurisdiction accorded to politicians and other authorities. Constitutional and legal rules are examined when defendants are authorities as the president of french Republic, members of the government, representatives and senators and other authorities. He concludes that privileges of jurisdiction exist in french Law but are less frequently found than in brazilian Law.